PERAN PEDAGOGI KONVENSIONAL DALAM PENGEMBANGAN KURIKULUM MADRASAH IBTIDAIYAH DI ERA DIGITAL - Afriantoni; Octarina, Vina; Putri, Darsy Dwi; Aswara; Ramadhani, Wulan (JISPE Journal of Islamic Primary Education, 2025)
This study aims to explore the contribution of traditional pedagogy to the development of the Madrasah Ibtidaiyah curriculum in the digital era. Data were collected through teacher interviews, analysis of curriculum documents, and field documentation. The research findings indicate that traditional pedagogy continues to play a crucial role in shaping students' character and morals, while digital learning serves as a complement and reinforcement. The synergy between conventional methods and digital technology produces a curriculum that balances Islamic values and 21st- century competencies. This study emphasizes that traditional pedagogy does not need to be replaced, but rather revitalized to align with the development of a digital-based curriculum in Madrasah Ibtidaiyah.